2016
DOI: 10.3126/jssn.v18i3.15301
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tamsulosin in relieving double-J stent-related symptoms: a randomized controlled study

Abstract: Introduction: Ureteral stent placement is an increasingly common procedure in urological practice.They are used for both prevention and treatment of ureteral obstruction. Despite improved design and materials, many patients still develop stent-related symptoms which commonly affect quality of life and sometimes necessitate early removal. Tamsulosin improves stent-related symptoms and quality of life, and can be applied in routine clinical practice. In the present study, the effect of Tamsulosin in improving do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…At the time of DJ removal there was significant difference noted in all the parameters. 18 This study also showed similar results at the time of DJ removal. At the time of discharge, Thakur et al didn't show any difference between the two groups but in this study there was significant difference noted.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…At the time of DJ removal there was significant difference noted in all the parameters. 18 This study also showed similar results at the time of DJ removal. At the time of discharge, Thakur et al didn't show any difference between the two groups but in this study there was significant difference noted.…”
Section: Discussionsupporting
confidence: 78%
“…Each patient filled a written form on IPSS, at the time of discharge and on the day of stent removal; with zero being least and 35 being the maximum out of 35 score. With the help of IPSS individuals are further divided into mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe symptoms (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).QoL is scored from 0-6, in which zero being best goal and 6 states that patient is in the terrible condition. Visual analogue scale (VAS) ranges from one to 10, one being the least and 10 being the maximum pain which he/she has never experienced.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed option for the cure of this disease and to make blood flow better is to use a bioengineered vein (silver microchannel) in the varicose vein. There are similar examples of stent implantation [ 82 , 83 , 84 , 85 ]. The bioengineered blood vessel also appears to be safe for dialysis process.…”
Section: Resultsmentioning
confidence: 99%
“…The studies have shown that antimuscarinics and alpha-blockers can help to improve lower urinary tract symptoms due to DJStent 1,7 . Compared to the placebo, Tamsulosin helps individuals with DJ stents reduce stentrelated symptoms and improve quality of life 8,9 . In a clinical trial, Tamsulosin and Solifenacin were compared with placebo; Tamsulosin increased DJSrelated irritative symptoms by 7.68 ± 3.66 and Solifenacin by 6.62 ± 3.92, which indicates that IPS irritative scores were higher than placebo 6 .…”
Section: Introductionmentioning
confidence: 99%